"Sorry, what did you say?" Communicating defibrillator retrieval and use in OHCA emergency calls. - Perera, Niru; Ball, Stephen; Birnie, Tanya; Morgan, Alani; Riou, Marine; Whiteside, Austin; Perkins, Gavin D; Bray, Janet; Fatovich, Daniel M; Cameron, Peter; Brink, Deon; Bailey, Paul; et al. (Elsevier, 2020)
BACKGROUND: The defibrillator prompt, which directs callers to retrieve a defibrillator during out-of-hospital-cardiac arrest, is crucial to the emergency call because it can save lives. We evaluated communicative effectiveness of the prompt instated by the Medical Priority Dispatch System ™ version 13, namely: if there is a defibrillator (AED) available, send someone to get it now, and tell me when you have it.